Comparing measured with simulated vertical soil stress under vehicle load: Are the measurements or the models wrong? - Keller, Thomas; Lamandé, Mathieu; Arvidsson, Johan; Berli, Markus; Ruiz, Siul; Schjønning, Per; Selvadurai, Patrick (Agrociencia Uruguay, 2012)
The load transfer within agricultural soil is typically modelled on the basis of the theory of stress transmission in elastic media, usually in the semi-empirical form that includes the “concentration factor” (v). Measurements of stress in soil are needed to evaluate model calculations, but may be biased because transducers do not read true stresses. The aim of this paper was to measure and simulate soil stress under defined loads. First, we investigated the accuracy of the transducers in situ by measuring stress at high spatial and temporal resolution at 0.1 m depth under a known load. Stress in the soil profile at 0.3, 0.5 and 0.7 m depth was measured during wheeling at field capacity on five soils (13-66% clay). Stress propagation was then simulated with the semi-analytical model, using vertical stress at 0.1 m depth estimated from tyre characteristics as upper boundary condition, and v was obtained at minimum deviation between measurements and simulations. The transducer readings over-predicted the true vertical stress by 10%. Consequently, the measured stresses were corrected before further analysis. For the five soils, we obtained an average v of 3.9 (for stress propagating from 0.1 to 0.7 m depth). This was not significantly different from v = 3, i.e. v for homogenous, isotropic and linear-elastic material. We noted that v was strongly dependent on the accuracy of stress measurements, and on the upper stress boundary condition used for simulations. Finite element simulations indicate that for an elasto-plastic layered soil (topsoil over plough pan over subsoil) propagation of vertical stresses is not appreciably different from that in a homogeneous isotropic and linear-elastic soil unless layers with (unrealistically) high soil stiffness are considered. Our results highlight the importance of accurate stress readings and realistic upper model boundary conditions, and suggest that actual stress propagation was in line with predictions according to elastic theory for the conditions investigated.